1997
DOI: 10.2527/1997.754910x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish meal in beef cattle diets on growth performance, carcass characteristics, and fatty acid composition of longissimus muscle.

Abstract: We investigated the effects of fish meal (FM) in beef cattle diets on growth performance, carcass characteristics, and fatty acid (FA) composition of longissimus muscle in 63 yearling steers (335 +/- 23 kg). High-moisture corn and alfalfa silage diets were supplemented with either a corn gluten/blood meal mixture or FM at 10% of the diet. Fish meal contained (as-is basis) 5.87 g/kg eicosapentaenoic acid (EPA) and 9.84 g/kg docosahexaenoic acid (DHA). Seven strategies were developed to feed either a control die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
2
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 37 publications
7
55
2
4
Order By: Relevance
“…Similar results have been obtained with fish meal enriched diets. These results showed that preferential incorporation of C20:5n-3 and of C22:6n-3 in lipids of Longissimus thoracis was to the detriment of n-6 PUFA, especially of C20:4n-6 [65].…”
Section: Effects Of Ruminant Feeding On the Nutritional Value Of Meatsmentioning
confidence: 77%
“…Similar results have been obtained with fish meal enriched diets. These results showed that preferential incorporation of C20:5n-3 and of C22:6n-3 in lipids of Longissimus thoracis was to the detriment of n-6 PUFA, especially of C20:4n-6 [65].…”
Section: Effects Of Ruminant Feeding On the Nutritional Value Of Meatsmentioning
confidence: 77%
“…In cattle fed linseed and fish oils, concentrations of EPA, DHA, and C18:3 increased in muscle phospholipids (Table 3), but the oil supplementation did not affect growth performance and feed intake compared to the control group (Scollan et al 2001a). Mandell et al (1997) found that feeding fishmeal significantly increased concentration of n-3 fatty acids including EPA and DHA in longissimus muscle. Jiang et al (1996) doubled the CLA content of milk from 5.04 to 11.28 mg g -1 fat by feeding a concentrate-toroughage ratio of 65:35 to dairy cows as compared to a 50:50 ratio.…”
Section: Increasing Desirable Fatty Acids In Beef Through Dietary Supmentioning
confidence: 92%
“…Secondly, IM fat cannot be considered in isolation from its health effects and related consumer concerns and its fatty acid (FA) profile has to be taken into consideration (Mazier and Jones, 1991;Simopoulos, 1991Simopoulos, , 2002Ulbricht and Southgate, 1991). Many studies have shown that fat partitioning (in the sense of amount and distribution) among the depots is influenced by several factors such as breed or genotype (Callow, 1962;Wright and Russel, 1984;HuertaLeidenz et al, 1993), sex or physiological status (Kazala et al, 1999;Malau-Aduli et al, 2000), age or live weight (Truscott et al, 1983;Rule et al, 1995), feeding (Mandell et al, 1997;Bas and Morand-Fehr, 2000) and anatomical location (Hood and Allen, 1975;Truscott et al, 1983), and that FA composition could be also influenced by the aforementioned factors and their interactions mainly related to animal's fat content (Nürnberg et al, 1998(Nürnberg et al, , 1999De Smet et al, 2004).…”
Section: Introductionmentioning
confidence: 99%